Gingivitis in Primary School Children of Bangladesh - Mishu, Masuma Pervin; Hubbard, Richard Marshal; Haque, Sejuty; Sayeed, M Abu; Imam, Syed Touseef; Khanam, Parvin Akhter; Begum, Tanjima; Khan, Mahfujul Haq (Ibrahim Medical College Journal, 2010)
Though early diagnosis and intervention of gingivitis in school children can eliminate progression to frank periodontal diseases, no such measures in Bangladesh are in place to detect gingivitis at an early stage in school children. This survey was conducted in 2007 in the primary schools of rural, suburban and urban areas of Bangladesh to evaluate oral hygiene with special emphasis on gingivitis prevalent among 6-13 years school children. The clinical examination of the gingiva was carried out using a mouth mirror and a periodontal probe. A total of 1,820 primary school students (m/f = 946/ 873) took part in the investigation. The crude prevalence of gingivitis, AS* and plaque were 17.5%, 9.2% and 56.0% respectively. The prevalence of gingivitis was significantly higher in males than females (20.3 vs. 14.3%, p<0.001), lower than upper social class (21.1 vs. 12.6%, p<0.001) and in rural than urban plus suburban children (22.5 vs. 15.1%, p<0.001). Likewise, the prevalence of AS and plaque were significantly higher in males, lower social class and rural children. Significantly lower prevalence of gingivitis, AS and plaque was found among those who used tooth brush and tooth paste than those who did not (15.4% vs 22.4%, p<0.001). The study concludes that the prevalence of oro-dental diseases is high in Bangladeshi children. The male children of low social class of rural communities are the most vulnerable group. Ibrahim Med. Coll. J. 2009; 3(2): 71-74 Key Words: Gingivitis, primary school children, oral health education. DOI: 10.3329/imcj.v3i2.4221